Composite Floor Chair Waste Mangrove Fruit Flour - Pungkas Prayitno; Joni Arif; Syaiful Arif (Universitas Muhammadiyah Sidoarjo, 2022)
One of the business sub-sectors that is capable of driving trade and development in Indonesia is the Handicraft Industry. One such craft industry is to utilize the potential of mangrove forests as economic management that manages with expertise, as well as creative, innovative, and commercial ideas so that it fosters interest and encourages people to develop ideas. Seeing from the potential availability of raw materials, this innovation is intended to utilize propagules as composite reinforcing materials, this innovation is carried out with the aim to model the floor chairs with propagules (Rhizophora mangrove fruit). This modeling uses the mixing of resin and powder propagules. The results show that it can be done by modeling floor chairs MangKoe using molds. This chair can hold back loads up to 70 kg.